Humanismo na era digital: um debate a partir da Ciência da Informação e Humanidades Digitais - Carlos, Caliel Luis Dolci (Universidade Federal de São Carlos, 2022)
The diversity of elaborations and conceptions that somehow understand trends towards a digital world reveal the need to situate an enlightening background, in which humanism in the digital can be explored and dis-cussed. In this environment, the formulations of Information Science are framed in the integration with Digital Humanities, engendering interesting perspectives and investigative possibilities, as a way of observing how Information Science dialogues with Digital Humanities to sustain human-ism in the digital age. In this perspective, the general objective of this study is to understand, based on Brazilian research that brings together Information Science and Digital Humanities, the thinking that supports humanism in the digital age. This is an exploratory and descriptive study, with a qualitative approach, based on bibliographic research. It was ob-served that the digital wave enters the humanities, making the discussion environment relevant and necessary, culminating in a process of self-reflection, in which the increasingly present intertwining between man and technology is foreseen. In this sense, transdisciplinarity takes center stage, by breaking down barriers between disciplines, in the search for adequate solutions to the needs of the digital age. Studies in Information Science from the perspective of Digital Humanities should consider the humanities in a broad sense. Consider, too, the creative and critical role of the Digital Humanities in the history of thought, from what can be done to humanisms in accordance with the introduction of new technolo-gies.
Humanism in the digital age: a debate based on Information Science and Digital Humanities
Keywords: Ciência da Informação; Humanidades Digitais; Humanismo; Era digital; Information Science; Digital Humanities; Humanism; Digital age; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA